2007
DOI: 10.1074/jbc.m703344200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Biosynthetic Gene Cluster in Rice for Momilactones

Abstract: Rice diterpenoid phytoalexins such as momilactones and phytocassanes are produced in suspension-cultured rice cells treated with a chitin oligosaccharide elicitor and in rice leaves irradiated with UV light. The common substrate geranylgeranyl diphosphate is converted into diterpene hydrocarbon precursors via a two-step sequential cyclization and then into the bioactive phytoalexins via several oxidation steps. It has been suggested that microsomal cytochrome P-450 monooxygenases (P-450s) are involved in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
276
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(282 citation statements)
references
References 35 publications
5
276
0
1
Order By: Relevance
“…In previous research, the quantification of momilactones A and B was reported using HPLC (Lee et al 1999;Shimura et al 2007;Lee et al 2002;Kong et al 2004;Kim et al 2007;Kato-Noguchi and Ota 2013). However, their contents can also be determined by GC-MS, which have been noted in in several reports (Matsuyama 1983;Fukuta et al 2007;Kodama et al 1988), as well as in this study, using standard momilactones A and B to compare their retention times, mass spectra, and fragments.…”
Section: Contents Of Momilactones a And Bmentioning
confidence: 88%
“…In previous research, the quantification of momilactones A and B was reported using HPLC (Lee et al 1999;Shimura et al 2007;Lee et al 2002;Kong et al 2004;Kim et al 2007;Kato-Noguchi and Ota 2013). However, their contents can also be determined by GC-MS, which have been noted in in several reports (Matsuyama 1983;Fukuta et al 2007;Kodama et al 1988), as well as in this study, using standard momilactones A and B to compare their retention times, mass spectra, and fragments.…”
Section: Contents Of Momilactones a And Bmentioning
confidence: 88%
“…Furthermore, the gene for OsKSL4 is found in the rice genome near that for the syn-CPP synthase (OsCPS4), 4 along with those for a dehydrogenase and cytochromes P450 also involved in momilactone biosynthesis. 5 Such secondary metabolism gene clusters are unusual in plants and generally are taken as an indication of strong selective pressure for production of the resulting compound operating over evolutionarily long timescales. 6 Together these findings suggest OsKSL4 has served as a syn-pimaradiene specific synthase for an extended period of time, with no selective pressure to retain catalytic features in its active site for more complex reaction mechanisms.…”
mentioning
confidence: 99%
“…D) Both CYP99A2 & 3 can convert C19 of syn-pimaradiene to a carboxylic acid, although this olefin can be alternatively hydroxylated at C3β by CYP701A8 or C7β by CYP76M8. The C19 oxidation catalyzed by CYP99A2 & 3 is relevant to momilactone biosynthesis (Shimura et al, 2007), while those catalyzed by CYP701A8 and CYP76M8 may be relevant as well (Kitaoka et al, submitted).…”
Section: Resultsmentioning
confidence: 99%
“…Many of these genes were found to be coregulated, specifically inducible by the fungal cell wall component chitin, as well . Subsequently, genetic (RNAi) evidence was reported indicating a role for the CYPs from the chromosome 4 cluster in momilactone diterpenoid metabolism (Shimura et al, 2007), consistent with the role of the co-clustered OsCPS4 and OsKSL4 [Figure 3 ]. This information was particularly useful in enabling focused investigation of CYPs -i.e., rather than investigating all >350 CYP found in the rice genome, we then simply targeted those from the diterpenoid biosynthesis clusters, along with the few others that exhibited inducible transcription (15 total).…”
Section: Investigation Of Rice Cyps In E Coli: Enabled By Gene Synthmentioning
confidence: 95%
See 1 more Smart Citation